Incorporating Outdoor and Environmental Ethics in Your Program - Matthews, Bruce E.; Coalition for Education in the Outdoors, Cortland, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
Outdoor ethics are primarily concerned with appropriate behaviors of participants as they pursue outdoor recreation activities. Environmental ethics are primarily concerned with developing a more personal sense of stewardship by all members of society, individually and collectively, regarding the use of the environment. The four general categories of environmental ethics are: (1) anthropocentrism, in which choices are based on what is of most benefit to humankind; (2) sentientism, centered on those beings capable of being aware of pleasure and pain; (3) biocentric individualism, in which every living thing has equal defendable interests; and (4) holistics, which considers the welfare of a system of living and non-living things. There are also four stages of environmental awareness which lead to the development of an environmental ethic. In the "awareness" stage, people are aware that a problem exists, but figure someone else will take care of it. During "realization," there is concern that a major part of the problem is a world population which is too large to support. In the "shallow ecology" stage, people realize that society is facing a serious problem, but assume that technology, economics, or politics will solve the problem. The final stage of "deep ecology" sees preserving the integrity of the ecosystem as the major goal. The document includes an outdoor ethics worksheet for outdoor educators to use with students to help them develop ethical guidelines prior to an outdoor trip. A list of 73 selected readings, newsletters, and journals on outdoor and environmental ethics also are provided. (KS)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Conservation (Environment); Ecology; Elementary Secondary Education; Environment; Environmental Education; Ethics; Instructional Materials; Outdoor Education; Program Development; Opinion Papers; Reference Materials, Bibliographies